Fault Diagnosis of Wind Turbine Gearbox based on Non-linear Short-time Fourier Transform and Time-domain Synchronization Average - Zuda Wang; Jian'gang Chen; Ronggen Wu; Zhen Zhang; Haiyang Cai; Guodong Sun (Jixie chuandong)
In view of the problem of ambiguity in the frequency spectrum of the vibration signal of the wind power gearbox under variable working conditions，and the traditional time-domain synchronous averaging method，the key phase signal and speed stability requirements are required. A time-domain synchronous averaging method that can track the instantaneous frequency of variable-speed vibration signals without key phase signals is proposed. This method uses non-linear short-time Fourier transform（NLSTFT） to obtain the instantaneous frequency curve of the variable speed gearbox vibration signal，and integrates to obtain the instantaneous phase curve. Resample the original signal in the angular domain according to the instantaneous phase to obtain the order signal. Finally，the order signal is processed by TSA for gear fault diagnosis. Based on the measured data of the gearbox of a unit，the validity and engineering practicability of the proposed method in the fault diagnosis of wind power gearbox are effectively verified.